One for CO 2 Preparation method and application of catalyst for preparing higher carbon alcohols by hydrogenation catalytic conversion

By combining Fe-based catalyst with metal oxide, a carbon layer-coated catalyst was prepared, which solved the problems of low conversion rate and high by-product selectivity in the C2+ alcohol reaction for hydrogenation of CO2, and achieved efficient high-carbon alcohol generation and Low by-product selectivity, suitable for large-scale production.

CN118681572BActive Publication Date: 2024-12-20SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410698704.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2024-12-20
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

In the prior art, the reaction to prepare C2+ alcohol with hydrogenation of CO2 has problems with low conversion rate and high selectivity of by-products. The thermodynamic stability and kinetic inertness of CO2 lead to uncontrollable reactions, making it difficult to match complex intermediates, and it is difficult to achieve efficient catalytic conversion. .

Method used

The Fe-based catalyst is combined with metal oxides, and the catalyst is prepared by mixing and grinding of iron ion precipitant, carbon-containing organic matter and metal additives, microwave treatment and calcination, forming a carbon-layer-coated Fe-based catalyst to regulate the Fe-based catalyst and metal oxidation. The interface interaction between objects improves the activation ability of CO2.

Benefits of technology

The high carbon alcohol generation with high CO2 conversion rate and high carbon atom selectivity is achieved, the by-product selectivity is low, the reaction initial phase of the catalyst is Fe3O4 and Fe3C, and the proportions of iron, carbon and metal oxides are reasonably distributed, which improves the Spatial-temporal yield of C2+ alcohol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004870462750000071
    Figure BDA0004870462750000071
  • Figure BDA0004870462750000081
    Figure BDA0004870462750000081
  • Figure HDA0004870462760000011
    Figure HDA0004870462760000011
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst synthesis and application, and specifically relates to a catalyst for CO 2 Preparation method and application of catalyst for hydrogenation catalytic conversion to produce high carbon alcohols. The preparation process of the present invention is: weigh appropriate amount of iron ion precipitant, metal auxiliary agent, iron salt and appropriate amount of carbon-containing organic compound, directly carry out mechanical grinding, after sufficient grinding, dry the mixture to obtain an iron precursor containing metal auxiliary agent, then, impregnate a salt compound of an element in group IIIA, IIIB, IVB, VIB, VIIB, VIII, IB, IIB into the iron precursor containing auxiliary agent, microwave treatment, drying, calcination to obtain catalyst. The catalyst prepared by the present invention is used for CO 2 The hydrogenation reaction has high selectivity for alcohol products, especially high-carbon alcohols with more than 2 carbon atoms. The carbon layer plays a key role in the interfacial interaction between Fe and oxides, making the catalyst more susceptible to C-O activation and C-C coupling, thereby obtaining a very high yield of high-carbon alcohols. The method is simple, low-cost, can be prepared on a large scale, and has good prospects for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst synthesis and application, and specifically relates to a method for preparing a catalyst for catalytic conversion of CO2 to produce higher carbon alcohols and its application. Background Art

[0002] The excessive use of traditional carbon-based energy (coal, oil, natural gas, etc.) has caused a sharp increase in the concentration of CO2 in the atmosphere, causing global climate change and environmental pollution. In recent years, researchers have continuously turned their attention to CO2 capture, utilization and storage (CCUS) technology that can make rational use and recycling of CO2. Among them, converting CO2 into high-value-added chemicals by thermal catalysis not only helps to alleviate environmental problems, but also realizes the resource utilization of CO2, which has important economic value and research significance (J.Environ Chem Eng, 2022, 10, 106962). Among them, alcohol chemicals, including ethanol and other high-carbon alcohols (C 2+ Alcohol), as one of the most important chemical raw materials, is widely used in pesticides, medicine, chemicals, building materials, automobiles and other industries, and can also be used as fuel, fuel additives to increase octane number and energy storage materials, etc. It is a clean energy with good development prospects (Chem, 2021, 7, 849-881). However, due to the thermodynamic stability and kinetic inertness of CO2, its chemical properties are very stable, and CO2 hydrogenation to prepare C 2+ The alcohol reaction involves multiple key and complex processes such as CO dissociation and insertion, CC coupling and CH formation, which leads to problems such as uncontrollable reaction and difficult matching of complex intermediates, making it difficult to efficiently catalyze the conversion of C 2+ There are still huge challenges for alcohol.

[0003] In recent years, CO2 hydrogenation to C 2+ A lot of research has been done on the production of alcohols, but most of them are based on Cu-based catalysts, precious metal catalysts, and Co-based or Mo-based catalyst systems (Angew. Chem. Int. Ed, 2022, 61, e202109027. ACS Catal, 2020, 10, 5250-5260. ACS Catal. 2020, 10, 14694-14706. Chem. Sci. 2019, 10, 3161. J. Catal. 2015, 36, 252.). Most of these types of catalyst systems have the problems of low conversion rate and high by-product selectivity. 2+The key to alcohol synthesis lies in the growth of CC bonds, and previous reports have shown that Fe-based catalysts have good CC coupling ability (Fuel, 2021, 296, 120689). In addition, metal oxide catalysts can provide good catalytic activity due to their adjustable valence states and the interfacial effects generated when they are combined with other components (Catalysts. 2022, 12, 450). Summary of the invention

[0004] In order to solve the technical problems existing in the prior art, the applicant envisions to design and develop a method for catalytic conversion of CO2 to C using the good CC coupling ability of Fe-based catalysts and the ability of metal oxides to activate CO2. 2+ Therefore, the present invention aims to provide a method for preparing a catalyst for the catalytic conversion of CO2 to produce higher alcohols with high CO2 conversion rate and selectivity for higher alcohols with carbon atoms greater than or equal to 2, and its application.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing a catalyst for catalytic conversion of CO2 to produce higher alcohols, the preparation method comprising the following steps:

[0007] (1) Weighing an iron ion precipitant, carbon-containing organic matter, iron salt and metal additive, mixing and grinding until iron is completely precipitated, and drying at 80-150° C. for 8-12 h (preferably at 100-120° C. for 12 h) to obtain an additive-containing iron precursor;

[0008] (2) adding a salt compound of a metal oxide to deionized water to prepare a solution, taking an appropriate amount of the obtained solution to fully impregnate the iron precursor containing the additive obtained in step (1), and then subjecting the mixture to microwave treatment (preferably in a microwave oven at 1000W-1200W for 2-5min), drying at 80-120°C for 8-12h (preferably drying at 100°C for 8-12h), and calcining at 350°C-750°C under N2 atmosphere for 2-8h (preferably calcining at 550-750°C for 2-4h) to obtain a catalyst for catalytic conversion of CO2 to prepare higher alcohols;

[0009] The metal in the salt compound of the metal oxide is selected from at least one of the elements of groups IIIB, IVB, VIB, VIIB, VIII, IB, IIB, and IIIA, such as one or more of the elements La, Ce, Ti, Zr, Mo, Co, Mn, Ni, Cu, Zn, and Ga.

[0010] The carbon-containing organic matter is selected from at least one of glucose, citric acid, urea and furfural.

[0011] Furthermore, in step (2), "taking an appropriate amount of the obtained solution to fully impregnate the iron precursor containing the additive obtained in step (1)" needs to be subjected to a water saturation experiment first to determine the amount of solution for impregnation. The "appropriate amount" mentioned above refers to the amount of solution that can just impregnate the iron precursor containing the additive obtained in step (1) after the water saturation experiment.

[0012] Furthermore, the iron salt is ferric nitrate nonahydrate.

[0013] Furthermore, the iron ion precipitant is ammonium bicarbonate.

[0014] Furthermore, the initial reaction phases of the catalyst for catalytic conversion of CO2 hydrogenation to produce high-carbon alcohols prepared by the above method are Fe3O4 and Fe3C, the mass of iron in the catalyst accounts for 40%-60% of the mass of the catalyst, the carbon content accounts for 10%-30% of the mass of the catalyst, the mass of the metal corresponding to the metal additive accounts for 0.1%-5% of the mass of the catalyst, and the mass of the metal corresponding to the salt compound of the metal oxide accounts for 4.5%-30% of the mass of the catalyst.

[0015] Furthermore, the mass of iron in the catalyst accounts for 45%-55% of the mass of the catalyst, the carbon content accounts for 15%-30% of the mass of the catalyst, the mass of the metal corresponding to the metal additive accounts for 0.5%-2% of the mass of the catalyst, and the mass of the metal corresponding to the salt compound of the metal oxide accounts for 4.5%-10% of the mass of the catalyst.

[0016] Furthermore, the salt compound of the metal oxide is one or more of nitrate, carbonate, and bicarbonate, preferably nitrate, and more preferably zirconium oxynitrate hydrate, cerium nitrate hexahydrate, or lanthanum nitrate hexahydrate.

[0017] Furthermore, the metal additive is a salt compound of at least one of alkali metal group IA, transition metal groups IIIB, IVB, VIB, VIIB, VIII, IB, and IIB, and the molar ratio of the metal in the metal additive to the iron in the iron salt is 1:(1-15), preferably 1:(6-12).

[0018] Furthermore, the metal additive is one or more of nitrate, carbonate, bicarbonate, hydrochloride, and sulfate, preferably bicarbonate, and more preferably potassium bicarbonate or sodium bicarbonate.

[0019] Furthermore, in step (1), the grinding is performed in a ball mill at 600-700 rpm for 2-4 hours.

[0020] Furthermore, the above calcination is carried out in a tubular furnace, and during calcination, the temperature is raised to the corresponding calcination temperature at a heating rate of 0.5-5°C / min.

[0021] The present invention also provides the use of the catalyst obtained by the above preparation method in the reaction of catalytic conversion of CO2 hydrogenation to produce higher carbon alcohols.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The catalyst prepared by the present invention has a high CO2 conversion rate. 2+ The space-time yield of alcohol can be as high as 356.5 mg g cat -1 ·h -1 Above, and the by-product selectivity is low.

[0024] 2. In the catalyst prepared by the present invention, since the Fe-based catalyst coated with a carbon layer is formed after calcination, the interface interaction between the Fe-based catalyst and the metal oxide is reasonably adjusted, so that the two can perform their respective functions and activate CO2 to a greater extent to convert it into C 2+ alcohol.

[0025] 3. The synthesis method of the invention is simple, low in cost, highly economical, suitable for large-scale production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the fresh catalyst prepared in Example 1 of the present invention. It can be seen from the image that the surface of the fresh catalyst is obviously coated with a carbon layer;

[0027] Figure 2 XRD spectrum of the fresh catalyst prepared in Example 1 of the present invention; it can be seen that the main phases of the freshly prepared catalyst are Fe3O4 and Fe3C, and Fe3C has a stronger characteristic diffraction peak, indicating that due to the introduction of the carbon layer, on the one hand, it can play a self-reduction role and reduce the Fe2O3 phase to Fe3O4, and on the other hand, it can significantly promote the carbonization of Fe to form an iron carbide phase, which is beneficial to the CO2 hydrogenation reaction.

[0028] Figure 3 The Fe 2p XPS spectrum of the catalyst prepared in Example 1 of the present invention shows that the fresh catalyst has a significant Fe-C characteristic peak near 706 eV, further proving that the introduction of the carbon layer promotes the formation of iron-carbon compounds.

[0029] Figure 4 The CO2-TPD graphs of the catalysts prepared in Example 1 of the present invention (blue line) and Comparative Example 1 (black line) show that the catalyst in Example 1 has a stronger CO2 desorption peak than that in Comparative Example 1, indicating that it has better CO2 adsorption capacity and can adsorb more CO2 to promote hydrogenation reaction under the same reaction conditions. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described in detail below through specific embodiments and drawings.

[0031] In the following examples, when impregnating the zirconium oxynitrate hydrate / cerium nitrate / lanthanum nitrate solution onto the precursor by the impregnation method, a water saturation experiment treatment is required first to determine the amount of solution that can just impregnate the precursor.

[0032] Example 1 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0033] Weigh 24.24g of ferric nitrate nonahydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758g of ammonium bicarbonate and 30.2601g of citric acid, place the above raw materials in a ball mill at the same time, grind them mechanically at 600rpm for 2h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9995g of zirconium oxynitrate hydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst. The mass percentage contents of relevant elements in the catalyst were tested by ICP and XRF, and the results were as follows: Fe 48.9%, C 21.2%, Zr 5.3%, and Na 1.2%.

[0034] Example 2 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0035] Weigh 24.24g of ferric nitrate nonahydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758g of ammonium bicarbonate and 12.9712g of glucose, place the above raw materials in a ball mill at the same time, grind them mechanically at 700rpm for 2h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9995g of zirconium oxynitrate hydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst.

[0036] Example 3 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0037] Weigh 24.24g of ferric nitrate nonahydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758g of ammonium bicarbonate and 4.3243g of urea, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 2h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9995g of zirconium oxynitrate hydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst.

[0038] Example 4 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0039] Weigh 24.24g of ferric nitrate nonahydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758g of ammonium bicarbonate and 6.9181g of furfural, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 3h, then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9995g of zirconium oxynitrate hydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, heat the dried sample to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcine it at 750℃ for 2h to obtain the catalyst.

[0040] Example 5 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0041] Weigh 24.24g of ferric nitrate 9hydrate, 0.51g of potassium bicarbonate (the molar ratio of iron to potassium is 12:1), 17.0758g of ammonium bicarbonate and 30.2611g of citric acid, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 4h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9871g of cerium nitrate hexahydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 10h, and the dried sample is heated to 650℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 650℃ for 3h to obtain the catalyst. The mass percentage contents of relevant elements in the catalyst were tested by ICP and XRF, and the results were as follows: Fe 50.2%, C 23.4%, Ce 4.9%, K 1.0%.

[0042] Example 6 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0043] Weigh 24.24g of ferric nitrate 9hydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758g of ammonium bicarbonate and 30.2611g of citric acid, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 2h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9871g of cerium nitrate hexahydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 650℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 650℃ for 3h to obtain the catalyst.

[0044] Example 7 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0045] Weigh 24.24g of ferric nitrate nonahydrate, 0.84g of sodium bicarbonate (the molar ratio of iron to sodium is 6:1), 17.7873g of ammonium bicarbonate and 30.2611g of citric acid, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 2h, and then place them in an oven and dry them at 100℃ for 12h to obtain solid powder after drying. Then weigh 10.0g of lanthanum nitrate hexahydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1000W for 5min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 550℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 550℃ for 4h to obtain the catalyst. The mass percentage contents of relevant elements in the catalyst were tested by ICP and XRF, and the results were as follows: Fe 52.6%, C 24.9%, La 6.3%, Na 1.8%.

[0046] Example 8 A catalyst for catalytic conversion of CO2 to produce higher alcohols is prepared by the following method:

[0047] Weigh 24.24g of ferric nitrate nonahydrate, 0.84g of sodium bicarbonate (the molar ratio of iron to sodium is 6:1), 17.7873g of ammonium bicarbonate and 30.2611g of citric acid, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 4h, and then place them in an oven and dry them at 100℃ for 12h to obtain solid powder after drying. Then weigh 10.0g of lanthanum nitrate hexahydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1000W for 5min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 8h, and the dried sample is heated to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst.

[0048] Comparative Example 1

[0049] Weigh 24.24g of ferric nitrate nonahydrate, 0.42g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), and 17.0758g of ammonium bicarbonate, place the above raw materials in a ball mill at the same time, grind them mechanically at 650rpm for 2h, and then place them in an oven and dry them at 120℃ for 12h to obtain solid powder after drying. Then weigh 9.9995g of zirconium oxynitrate hydrate and dissolve it in 50mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, transfer the sample to a microwave oven, microwave it at 1200W for 2min, wait for it to cool naturally to room temperature, then place the sample in an oven and dry it at 100℃ for 12h, and the dried sample is heated to 750℃ at 2℃ / min in a tube furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst.

[0050] Comparative Example 2

[0051] Weigh 24.24 g of ferric nitrate nonahydrate, 0.42 g of sodium bicarbonate (the molar ratio of iron to sodium is 12:1), 17.0758 g of ammonium bicarbonate and 30.2601 g of citric acid, place the above raw materials in a ball mill at the same time, mechanically grind them at 650 rpm for 2 h, then place them in an oven and dry them at 120 °C for 12 h. The sample obtained after drying is heated to 750 °C at 2 °C / min in a tubular furnace under N2 atmosphere, and calcined at 750 °C for 2 h to obtain the catalyst.

[0052] Comparative Example 3

[0053] Weigh 24.24 g of ferric nitrate nonahydrate and dissolve it in 100 mL of deionized water. Place it in an oil bath at 80°C and slowly add a 2 mol / L sodium hydroxide solution to the solution until the pH reaches 9.1. Let it stand for 4 hours and wash the precipitate with deionized water until it is neutral (pH = 7.0), filter it, and dry the solid at 60°C for 12 hours. The dried sample is heated to 350°C at 2°C / min in a muffle furnace and calcined at 350°C for 4 hours to obtain a solid powder. Then weigh 14.99g of zirconium nitrate trihydrate and dissolve it in 100mL of deionized water to prepare a solution, take 1mL of the solution and impregnate it on 2.0g of the solid powder obtained above, and vacuum evaporate it at 90℃ on a rotary evaporator for 4h, then place the sample in an oven and dry it at 100℃ for 12h. The dried sample is heated to 750℃ at 2℃ / min in a tubular furnace under N2 atmosphere, and calcined at 750℃ for 2h to obtain the catalyst.

[0054] The catalysts obtained in Examples 1-8 and Comparative Examples 1-3 were used in the CO2 hydrogenation reaction test:

[0055] The catalyst was evaluated in a fixed bed reactor using a syngas ratio of H2:CO2:N2 = 67.75:22.25:10 (volume ratio), a pressure of 2.0 MPa, a reaction temperature of 340°C, and a reaction space velocity of 12 SL / (g cat h). All catalysts were reduced with pure hydrogen before testing at a temperature of 400°C and a reaction space velocity of 4SL / (g cat h), the time is 2h. The test data is the data obtained after the CO2 conversion rate is stable, and the reaction time is 100h.

[0056] The reaction performance of each catalyst is shown in Table 1:

[0057] Table 1 Catalytic performance of catalysts CO2 hydrogenation performance summary

[0058]

[0059]

[0060] Compared with the example, the difference in the preparation process of Comparative Example 1 is that no carbon-containing organic matter is added. From the reaction data, it can be seen that the conversion rate and C 2+ The yield of alcohols has decreased to a certain extent. Since the contact between the metal oxide and the Fe-based catalyst is too close, the mutual interaction between the interfaces is too strong, which limits the carbonization of Fe to form iron carbide during the reaction. Since iron carbide is an important active phase for CC coupling, the reduction of its content will reduce the formation of CC bonds, which is not conducive to C 2+ Alcohol production.

[0061] Compared with the example, the difference in the preparation process of Comparative Example 2 is that no metal oxide salt is added, resulting in no metal oxide in the catalyst. By comparing the reaction data, it can be seen that the CO2 conversion rate is significantly reduced. This is because the metal oxide, as an important component to promote the activation of CO2, plays a key role in improving the reaction activity. In addition, the absence of metal oxide leads to the disappearance of the metal-metal oxide interface, reducing the generation of C 2+ The alcohol is an important intermediate required for the production of the target product C 2+ The yield of alcohol was greatly reduced.

[0062] Compared with the examples, the difference in the preparation process of Comparative Example 3 is that the preparation method of the catalyst is changed from mechanical grinding to precipitation, and the metal oxide is impregnated onto the Fe-based catalyst by rotary evaporation. In addition, no carbon-containing organic matter is added in this comparative example. Since the mechanical grinding method can promote the electron transfer of the metal additive to Fe, increase the electron density on the Fe surface, and promote the formation of olefins, CO2 hydrogenation generates C 2+In the reaction mechanism of alcohol, olefins are first generated, and then olefins combine with CO to form a CO insertion mechanism, which is an important step in the generation of high-carbon alcohols. Compared with microwave treatment, rotary evaporation is not conducive to the formation of highly uniformly dispersed nanoparticles, which will cause particle agglomeration during the reaction and reduce reaction performance. Similarly, the carbon layer, as a key factor in regulating the interface effect, will also affect the structural changes of the catalyst during the reaction. Therefore, the catalyst has a significant reduction in both CO2 conversion rate and target product selectivity.

Claims

1. A method for preparing a catalyst for catalytic conversion of CO2 to produce higher alcohols, characterized in that: The preparation method comprises the following steps: Step (1): weighing an iron ion precipitant, carbon-containing organic matter, iron salt and metal additive, mixing and mechanically grinding until the iron is completely precipitated, and then drying at 80-150° C. for 8-12 hours to obtain an iron precursor containing additives; Step (2): adding a salt compound of a metal oxide to deionized water to prepare a solution, taking an appropriate amount of the obtained solution to fully impregnate the iron precursor containing the additive obtained in step (1), and then sequentially subjecting the mixture to microwave treatment, drying at 80-120°C for 8-12 hours, and calcining at 350°C-750°C under a N2 atmosphere for 2-8 hours to obtain a catalyst for catalytic conversion of CO2 to prepare higher carbon alcohols; The carbon-containing organic matter is at least one of citric acid, urea, glucose and furfural; The metal oxide salt compound is zirconium oxynitrate hydrate, cerium nitrate hexahydrate or lanthanum nitrate hexahydrate; The metal auxiliary agent is potassium bicarbonate or sodium bicarbonate.

2. The preparation method according to claim 1, characterized in that: The iron salt is ferric nitrate nonahydrate, and the iron ion precipitant is ammonium bicarbonate.

3. The preparation method according to claim 1, characterized in that: In step (1), the grinding is performed in a ball mill at 600-700 rpm for 2-4 hours.

4. The preparation method according to claim 1, characterized in that: The initial reaction phases of the catalyst for catalytic conversion of CO2 to produce higher carbon alcohols prepared in step (2) are Fe3O4 and Fe3C, the mass of iron in the catalyst accounts for 40%-60% of the mass of the catalyst, the carbon content accounts for 10%-30% of the mass of the catalyst, the mass of the metal corresponding to the metal additive accounts for 0.1%-5% of the mass of the catalyst, and the mass of the metal corresponding to the salt compound of the metal oxide accounts for 4.5%-30% of the mass of the catalyst.

5. The preparation method according to claim 1, characterized in that: In step (2), "taking an appropriate amount of the obtained solution to fully impregnate the iron precursor containing the additive obtained in step (1)" requires first conducting a water saturation experiment to determine the amount of solution for impregnation. The "appropriate amount" mentioned above refers to the amount of solution that can just impregnate the iron precursor containing the additive obtained in step (1) after the water saturation experiment.

6. Use of the catalyst obtained by the preparation method according to any one of claims 1 to 5 in the reaction of catalytic conversion of CO2 hydrogenation to produce higher alcohols.